Films CdS Grown on Porous Si Substrate - Diadenchuk, Alona; Дяденчук, Альона Федорівна; Дяденчук, Алена Федоровна; Kidalov, V. V. (My University, 2018)
In this work, CdS films were obtained on the technology of chemical surface deposition on porous semiconductor substrates. The morphology and chemical composition of the obtained structures were studied. The possibility of using CdS/porous-Si/p-Si heterostructures as photovoltaic solar energy converters is considered
Keywords: Films CdS; Porous substrate Si; Chemical surface deposition; Photoelectric converters